Fauna extraida en la exploración del barco M/N “Vikheim” al noroeste del Caribe colombiano - Álvarez-León, Ricardo (2003)
Crustaceans (5 families, 10 species) and fish (38 families, 101 species) were captured (October 27 through November 3, 1979) from the R/V “Vikheim” (Cruise 7901) in the Colombian Caribbean, at a 10-630 m, depth range (Metapeneopsis shrimp, 26 species of fishes new for the trawling bottom and, Squalus cubensis, Chlorophthalmus agassizi, and, Neoepinnula orientalis), new fishes records for the Caribbean of Colombia